Integrasi Payment Gateway Dalam Sistem Keuangan Sekolah - Rinda Cahyana; Muhammad Rikza Nashrulloh; Hary Sholahudin (Institut Teknologi Garut, 2026)
Madrasah Aliyah Ma'arif Cilageni Kadungora is a formal educational institution established specifically for senior high school education. Madrasah Aliyah certainly has supervision, a financial payment system for tuition fees, and other payment systems. One of the problems in managing financial data for tuition payments is that it is still done manually, through written records and conventional number management applications. The focus of the problem may be on data recording or recapitulation, which is time-consuming and has a high level of human error. The methodology used in creating this system is the Rational Unified Process (RUP) with four stages: Inception, Elaboration, Construction, and Transition. System modeling was performed using the Unified Modeling Language (UML), and the programming language used was PHP with the Laravel framework. The main objectives of this system are to facilitate schools in managing finances, reduce delays in tuition payments, and provide tuition payment information to parents or guardians of students via WhatsApp notifications. The results of the study show that students can make payments via Virtual Account, Bank Transfer, QRIS, or other methods. With the existence of Payment Gateway technology, it is proposed as a solution so that the payment process is automatically recorded in the madrasah's financial system, enabling schools to provide better services.